Effects of Hypoxic Stress on Tissue Structure and Gut Bacterial Community of Exopalaemon carinicauda - Xinlei ZHOU; Qingyang LI; Jiawei ZHU; Shumin XIE; Mintao WANG; Ting YANG; Chaofan XING; Huan GAO; Qingqi ZHANG; Panpan WANG (Progress in Fishery Sciences)
Exopalaemon carinicauda has the highest production in the Yellow Sea and Bohai Sea of China. Compared with those of other shrimp species, E. carinicauda has a short reproductive cycle, fast growth, and adaptability. The pond mono-culture and mixed culture mode is more common in small economic shrimp and can be used as an excellent biological material for crustacean biology research. Dissolved oxygen, an important environmental factor for aquatic animal survival, affects the growth, behavior, reproduction, immunity, and metabolism of aquatic animals and is highly susceptible to hypoxia due to high temperatures, flushing, water pollution, the expansion of the scale of aquaculture, high-density aquaculture, high temperatures, and climate change. Recently, studies have been conducted on the effects of hypoxia on aquatic animals, mainly focusing on immune response, energy consumption, respiration, and antioxidant character. Gill and hepatopancreas tissue are major organs in crustaceans and increasing evidence reveal that gut bacterial community are involved in host immune defense, nutrient absorption, and antioxidant processes. Therefore, investigating the effects of hypoxic stress on the tissue structure and gut bacterial community of E. carinicauda will help to elucidate the mechanism of the response of E. carinicauda to hypoxic environments, which will be useful for its healthy aquaculture. In this study, we collected gill, hepatopancreas, and gut tissues from experimental and control groups after 24 h of hypoxic stress (2.5±0.2) mg/L. The gills and hepatopancreas were sectioned and observed and the changes in gut bacterial community before and after hypoxic stress were analyzed using 16S rRNA gene sequencing. The experimental results showed that gill and hepatopancreas tissues underwent different degrees of damage after hypoxic stress; the gut bacterial community changed, some pillar and epithelial cells of gill tissues were disordered, the number of chloride cells was significantly reduced, chloride cells were changed from irregularly flattened to rounded, the secondary lamellae was aggravated, and the gill tissues changed their morphology and structure to alleviate the hypoxic stress. The number of storage cells in hepatopancreas tissues did not change significantly compared with that of the control group, the lumen contracted significantly, the morphology and structure of the entire hepatic tubule contracted, the volume of transport vacuole increased significantly and even ruptured, and the number of secretory cells decreased significantly. Although shrimp gut bacteria are numerous and diverse the vast majority of gut bacteria are reported to be concentrated in a few dominant bacterial phyla, such as Proteobacteria, Bacteroidetes, Actinobacteria, and Firmicutes. The richness and diversity of gut bacterial community of individuals in the experimental group changed significantly after hypoxic stress and Proteobacteria and Firmicutes were the dominant bacterial phylum in the guts of the control group, accounting for 81.42% and 11.18% of the total amount, respectively. The amounts of Bacteroidota and Actinobacteriota were significantly higher (P < 0.05), and that of Proteobacteria were significantly lower (P < 0.05) in the experimental group. At the family level, the numbers of Prevotellaceae and Lachnospiraceae were significantly higher (P < 0.05) in the experimental group than those in the control group. Rhodobacteraceae bacteria had a relative high abundance in the gut of healthy E. carinicauda and their amounts were significantly reduced after hypoxic stress. In addition, the numbers of some potential pathogenic bacteria were significantly higher (P < 0.05) in the experimental group. At present, multiple studies are being conducted on aquatic animals under hypoxic stress; however, the effects of hypoxic stress on the tissue structure and intestinal flora of E. carinicauda remains unexplored. In this study, we observed the damage of tissue structure and simultaneously analyzed the changes in intestinal flora of E. carinicauda under hypoxic stress, to deeply study the physiological response to stress under hypoxic conditions of E. carinicauda and provide basic scientific research on the actual production and cultivation of a novel species of E. carinicauda that is resistant to hypoxic conditions. This will provide basic scientific research information for the actual production and cultivation of novel hypoxia-tolerant varieties of E. carinicauda.